Significance of CEBPE Gene Promoter Polymorphism (Rs2239630 G > A) Assessment in Childhood B-cell Acute Lymphoblastic Leukemia. Issue 3 (20th February 2023) - Aref, Salah; El-Ghonemy, Mohamed; Shimaa, Hendawy; Darwish, Ahmad; Abdelmabood, Suzy; Khaled, Nada
Abstract : Background: A significant association has been reported between CEBPE gene promoter polymorphisms (rs2239630 G > A ) and the incidence of B-cell acute lymphoblastic leukemia (B-ALL). However, no previous study on this issue has been included among the Egyptian cohort of pediatric patients with B-ALL. Therefore, this study was designed to address the associations between CEBPE polymorphisms and susceptibility to B-ALL, as well as its impact on the outcome of B-ALL Egyptian patients with B-ALL. Patients and Methods: In the current study, we evaluated the rs2239630 polymorphism in 225 pediatric patients and 228 controls to assess the association of different rs2239630 genotypes with childhood susceptibility to B-ALL and the impact on the outcome of the patients. Results: The frequency of the A allele was significantly higher in the cases of B-ALL compared with the control group ( P = 0.004). By analyzing different genotypes for the predictive value of disease development, the GA and AA genotypes have been identified to be the highest among multivariate factors with an odds ratio of 3.330 (95% CI: 1.105-10.035). Likewise, the A allele was significantly associated with the shortest overall survival. Conclusions: CEBPE gene promoter polymorphism (rs2239630 G > A ) AA is frequently associated with B-ALL; and has the worst overall survival among the 3 genotypes, followed by the GA and GG genotypes ( P < 0.001)